2013
DOI: 10.1016/j.vaccine.2013.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the protective role of adaptive immunity to CHIKV/IRES a novel candidate vaccine against Chikungunya in the A129 mouse model

Abstract: Chikungunya virus (CHIKV), a mosquito-borne alphavirus, recently re-emerged in Africa and spread to islands in the Indian Ocean, the Indian subcontinent, and to South East Asia. Viremic travelers have also imported CHIKV to the Western hemisphere highlighting the importance of CHIKV in public health. In addition to the great burden of arthralgic disease, which can persist for months or years, epidemiologic studies have estimated case-fatality rates of ~0.1%, principally from neurologic disease in older patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 39 publications
(44 reference statements)
3
69
1
2
Order By: Relevance
“…Some of these observations, however, have been made under in vitro conditions. Here and in our previous work (12), observations have suggested that ADE may occur in CHIKV infection in mice with low IgG titers, below 10 4 . This important observation reveals the need for further work to provide indications on how to avoid ADE induced by vaccination.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Some of these observations, however, have been made under in vitro conditions. Here and in our previous work (12), observations have suggested that ADE may occur in CHIKV infection in mice with low IgG titers, below 10 4 . This important observation reveals the need for further work to provide indications on how to avoid ADE induced by vaccination.…”
Section: Discussionsupporting
confidence: 60%
“…We and others have demonstrated a clear correlation between antibodies and protection against CHIKV infection in both mice (10,12,49) and humans (50), highlighting the importance of antibody responses for immunity against CHIKV. This was also observed here: high anti-CHIKV antibody levels correlated inversely with viremia and foot swelling after challenge.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting. Antibody responses are known to correlate with protection against CHIKV (29)(30)(31)(32)(33)(34)(35)(36), but CD4 T cell responses may also be important (37)(38)(39). Thus, it was of importance to determine the potential immunological differences that our vaccine candidate might display.…”
Section: Discussionmentioning
confidence: 99%